2023
DOI: 10.1029/2023gl103612
|View full text |Cite
|
Sign up to set email alerts
|

Citizen Science Observation of a Gamma‐Ray Glow Associated With the Initiation of a Lightning Flash

Abstract: Strong electric fields inside thunderclouds accelerate electrons up to relativistic energy and cause several types of high-energy atmospheric phenomena. One example is terrestrial gamma-ray flashes (TGFs) coinciding with lightning discharges (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…Here we report this growing citizen science project and examples of successful gamma-ray glow observations. Our first scientific result from this citizen science project was published in Tsurumi et al, GRL 2023 [1], where we reported lightning discharges started in or near the electron acceleration site of a gamma-ray glow.…”
Section: Teruaki Enotomentioning
confidence: 79%
See 1 more Smart Citation
“…Here we report this growing citizen science project and examples of successful gamma-ray glow observations. Our first scientific result from this citizen science project was published in Tsurumi et al, GRL 2023 [1], where we reported lightning discharges started in or near the electron acceleration site of a gamma-ray glow.…”
Section: Teruaki Enotomentioning
confidence: 79%
“…Some data are remotely sent to the web server so researchers and citizen supporters can watch the realtime monitoring data. When a gamma-ray glow is detected with the count rate exceeding the predetermined threshold, an automatic alert in the server is sent to the public on Twitter [1].…”
Section: Teruaki Enotomentioning
confidence: 99%
“…The illogicalness of LNT theory for cancer induction is revealed by the fact that even though we humans reside in a sea of natural background ionizing radiation, we have not perished from Earth, but remain in large numbers. We are exposed to gamma-ray photons (related to cosmic rays 5 and thunderstorms 6 ) and other natural background radiation throughout our lives, including photons with energies 5 > 10 GeV. Unfortunately, some influential epidemiologists still rely on LNT models for cancer risk assessment.…”
mentioning
confidence: 99%